Ð’Ð»Ð¸ÑÐ½Ð¸Ðµ ÑÐºÑÑ‚Ñ€Ð°ÐºÑ‚Ð° Ñ…Ð¾Ñ€Ð¸Ð¾Ð½Ð° Ð½Ð° Ñ„ÑƒÐ½ÐºÑ†Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ð¾Ðµ ÑÐ¾ÑÑ‚Ð¾ÑÐ½Ð¸Ðµ Ð³ÐµÐ¿Ð°Ñ‚Ð¾Ñ†Ð¸Ñ‚Ð¾Ð² ÐºÑ€Ñ‹Ñ in vitro Ð¸ in vivo - Pashinsky, P. P.; Subbota, N. P. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2006)
There have been performed the experiments on studying the effect of chorion cryoextract (CC) on morphofunctional properties of isolated hepatocytes during hypothermic storage as well as a part of an organ during rats’ poisoning with CCl4. It has been shown that at hypothermic storage of hepatocytes in sucrose-saline medium a bioadditive as chorion cryoextract prolongs their viability that is confirmed by the indices of protein biosynthesis and the exclusion rate of supravital dye. Introduction of chorion cryoextract to the animals at CCl4 poisoning reduces the intensity of lipid peroxidation (decrease in MDA production), cytolysis indices, cholestasis, accumulation of toxic exchange products (bilirubin level decrease), increases the activity of antioxidative systems (activity of superoxide dismutase). Introduction of chorion biological preparations during poisoning of animals with CCl4 is more effective at the stages, preceding the development of hepatic insufficiency.